2009
DOI: 10.3748/wjg.15.5654
|View full text |Cite
|
Sign up to set email alerts
|

Shift work aggravates metabolic syndrome developmentamong early-middle-aged males with elevated ALT

Abstract: AIM:To examine whether shift work accelerates metabolic syndrome (MetS) development among early middle-aged males with elevated alanine aminotransferase (e-ALT). METHODS:A retrospective, observational followup study on MetS development at a 5-year interval was conducted using health examination data. Nine hundred and ninety six male employees not fulfilling MetS criteria at screening were enrolled. Age, MetScomponents, liver enzymes, serological markers for viral hepatitis, abdominal ultrasound, insulin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
3
19
1
Order By: Relevance
“…To our knowledge, the present study is the first that shows non diabetic NAFLD patients representing a higher serum ALT level are significantly more likely to have higher NAFLD grades. It has been previously shown that serum ALT is associated with insulin resistance in NAFLD patients [30] , but our finding is in a population after exclusion of diabetic patients. Another interesting finding of the current study is that abnormal ALT levels, independent to NAFLD severity grade, is significantly associated with insulin resistance.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…To our knowledge, the present study is the first that shows non diabetic NAFLD patients representing a higher serum ALT level are significantly more likely to have higher NAFLD grades. It has been previously shown that serum ALT is associated with insulin resistance in NAFLD patients [30] , but our finding is in a population after exclusion of diabetic patients. Another interesting finding of the current study is that abnormal ALT levels, independent to NAFLD severity grade, is significantly associated with insulin resistance.…”
Section: Discussioncontrasting
confidence: 54%
“…This makes our study unique. Some previous studies have suggested that elevated ALT levels and fatty livers were independently associated with increased risk of metabolic syndromes [29,30] . On the other hand, consistent to our results, a community-based study in Taiwan, a country with a relatively low prevalence of diabetes mellitus [31] showed no increased prevalence of metabolic syndrome for NAFLD patients with elevated ALT levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, we treated waist circumference as a confounder in the multivariate analysis (Table 5) because it has a decisive influence on the development of metabolic syndrome. On the other hand, occupational and lifestyle factors naturally affect dietary behaviors and thus affect body weight changes [19] and other factors of atherosclerosis which are important in MetS development, including total cholesterol, low density lipoprotein cholesterol, uric acid and insulin. Our present study focused on body weight changes, and although we controlled some occupational, lifestyle and baseline metabolic factors (not shown in tables), the detailed impact of these factors needs to be clarified by other investigations.…”
Section: Discussionmentioning
confidence: 99%